Personality development - Selvam, S.K. Panner (New delhi : S.B. nangia, 2010)
Success in any field, whether it is business, education, art or scientific invention is mainly dependent upon a person's motivation. Its importance in the field of education cannot be emphasized. Enormous amount of research has been done in this field, covering a wide range of issues like the psychological basis of motivation, types of motivation, inhibitory factors and ways to stimulate motivation. It is imperative for every teacher to know the dynamics of motivation. So that be could areas and chicaneries it properly. A lot of creativity and innovation are needed to face the challenges of modern times. A deep insight into the nature of the creative faculty and techniques to foster creativity are reflected in this book. Teacher's positive attitudes and their concern for quality are pivotal to the success of the educational enterprise and this book gives an upto date account of the research done in this field. Research studies such as efficacy of innovative approaches like ABL and ALM are explained in great detail. In sum, this book will prove to be an invaluable guide to every teacher, teacher educator and all those people interested in the development of the nation. This is a compiled edition. A school student as well as a researcher can find interesting material in this book. Most of the articles are contributions of eminent persons in the field of education. The very purpose of this edition is to make the students and the teachers know what is going on around them in the academic world. Even the entrepreneurs in the realm of education find it more beneficial. Some of the articles are modified or simplified versions.
Keywords: Child development -- India; Personality development -- India